Ransomware: What you need to know: a Joint report by Check Point and Europol (Europol Public Information, 2016)
In recent years, there has been a surge of ransomware. It’s been reported all over security blogs, tech website and even the news. It doesn’t seem to stop; in fact, it seems to be getting worse in both spread and sophistication